Mortality in acute pancreatitis with persistent organ failure is determined by the number, type, and sequence of organ systems affected. Issue 2 (19th April 2021) - Machicado, Jorge D.; Gougol, Amir; Tan, Xiaoqing; Gao, Xiaotian; Paragomi, Pedram; Pothoulakis, Ioannis; Talukdar, Rupjyoti; Kochhar, Rakesh; Goenka, Mahesh K.; Gulla, Aiste; Gonzalez, Jose A.; Singh, Vikesh K.; et al.
Abstract: Background: Persistent organ failure (POF) is the strongest determinant of mortality in acute pancreatitis (AP). There is a paucity of data regarding the impact of different POF attributes on mortality and the role of different characteristics of systemic inflammatory response syndrome (SIRS) in the risk of developing POF. Objective: We aimed to assess the association of POF dynamic features with mortality and SIRS characteristics with POF. Methods: We studied 1544 AP subjects prospectively enrolled at 22 international centers (APPRENTICE consortium). First, we estimated the association of onset, duration, and maximal score of SIRS with POF. Then, we evaluated the risk of mortality based on POF onset, duration, number, type, and sequence of organs affected. Analyses were adjusted for potential confounders. Results: 58% had SIRS, 11% developed POF, and 2.5% died. Early SIRS, persistent SIRS, and maximal SIRS score ≥ 3 were independently associated with higher risk of POF ( p  < 0.05). Mortality risk in POF was higher with two (33%, odds ratio [OR] = 10.8, 3.3–34.9) and three (48%, OR = 20.2, 5.9–68.6) organs failing, in comparison to single POF (4%). In subjects with multiple POF, mortality was higher when the cardiovascular and respiratory systems failed first or concurrently as compared to when the renal system failed first or concurrently with other organ ( p  < 0.05). In multivariate regression model, the number and sequence of organs affected in POF were associated with mortality ( p  < 0.05). Onset and duration of POF had no impact mortality. Conclusion: In AP patients with POF, the risk of mortality is influenced by the number, type, and sequence of organs affected. These results are useful for future revisions of AP severity classification systems. Key Summary: What is known? Persistent organ failure (POF; >48 h) is the strongest determinant of mortality in acute pancreatitis (AP). There is lack of evidence on the impact of different attributes of failing organs on AP mortality. The association of systemic inflammatory response syndrome (SIRS) characteristics with POF, has not been well studied. What is new here? Mortality risk in AP patients with POF is determined by the number, type, and sequence of organ systems affected. Multiple POF affecting the cardiovascular and respiratory systems first or concurrently carries the highest mortality in AP compared to the renal system. Involvement of the renal system as the first failing organ or concurrently with other organs during multiple POF is associated with lower mortality than respiratoy or cardiovascular systems as first failing organs. Onset and duration of POF are not associated with mortality in AP patients. SIRS on admission, persistent SIRS, and three to four SIRS criteria, are independently associated with higher risk of POF.